(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2023)
Wireless Sensor Networks (WSNs) are sensors capable of wireless networking, environmental monitoring, and signal processing. In WSN, there are several challenges and design problems, such as node deployment, routing, coverage, connection, and quality of service. Due to the massive number of sensor nodes in the WSN, routing can be viewed as a significant challenge. Energy, storage capacity, and power consumption are the most effective WSNs’ limitations. It is crucial to consider these restrictions while selecting routing protocols for wireless sensor nodes. The characteristics and network typology of the routing protocols can be used to classify them. Several performance approaches and algorithms are used to assess routing protocols’ performance. This manuscript studies and compares the energy efficiency and throughput of Low Energy Adaptive Clustering Hierarchy (LEACH) and Hybrid Energy Efficient Distributed (HEED); the most effective power-aware routing protocols by changing the packet size and node density. This study was performed through simulation by utilizing the MATLAB tool. The simulation results showed that LEACH outperformed HEED in terms of throughput by an average of 28.85%, whereas HEED saved energy by an average of 3.41% compared to the LEACH protocol.